Hydrogel-mediated direct patterning of conducting polymer films with multiple surface chemistries - Park, SooHyun (Advanced materials (Deerfield Beach, Fla.), 2014)
© 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.